Gender violence: public policies, upholding the fundamental right to non-discrimination and proposed solutions - Novoa Campos, Bruno (2016)
The author believes that the different forms of gender violence should be analyzed in light of the public policies established by the Peruvian State and its defense should focus on strengthening the fundamental right to non-discrimination. The author proposes creating the Technical Secretariat of Defense of Women’s Rights.